Kajian Literatur Pengembangan Instrumen Kemampuan Problem Solving Pada Materi Fisika (IPF: Inovasi Pendidikan Fisika, 2021)
Problem solving is a skill that students must possess in the 21st century, especially in physics subjects. The purpose of this literature review is to identify the development of problem-solving instruments in physics. This study examines journals in 2016-2021 with a qualitative approach using the bibliometric method. From analysis, results prove that the development of problem solving instruments is based on the demands of the 21st century and knowing the extent to which educators are successful in implementing learning innovations that are applied to the teaching and learning process. Problem solving instruments are in the form of tests and non-tests. The test questions were developed to pay attention to problem solving indicators such as Polya, J.L Doctor, Arends etc. The widely developed materials are Newton's Law of Kinematics, Effort and Energy, and Momentum and Impulse. The development methods that are widely used in making this product are the 4D and ADDIE methods. The problem solving instrument was tested and then analyzed for feasibility, including validity testing by experts, practical validity tests, reliability tests, t tests and the Wilcoxon Signed Ranked. Keywords: instrument test problem solving, physics, bibliometric